THE EFFECT OF TOYS ON FAST-FOOD PRODUCT PREFERENCES - Sabiha Kılıç; Kübra Müge Çakaröz; Leyla Bezgin Ediş (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The aim of the study is to examine the role of toys in 10-14 age group consumers being affected by fast food products. For this purpose, menu images of Burger King with toys, which include gender-oriented Barbie and car toys, and without toys, and menu images of Mc Donald's with toys, which include McDonalds' unisex toy, and without toys, were used. It was analyzed whether there is a difference between the effects of the menus with and without toys according to the gender and fast food consumption habits of the consumers in the 10-14 age group participating in the experiment. Galvanic Skin Response and Eye Tracking devices, which are neuro imaging techniques, were used in the study. Participants were shown a 38-second video consisting of Burger King and McDonalds' menu images with and without toys, and numerical data at the level of seconds and kiloohms (kohm) were obtained. Wilcoxon Sign Test was used to analyze the data. As a result of the analysis, it was determined that the participants were affected by the menus with and without toys according to their gender and fast-food liking. It was determined that there was no difference in the level of being affected by the toy and non-toy menus according to the fast-food consumption frequency and menu preferences of the participant